2021
DOI: 10.2147/jmdh.s330533
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between professional quality of life and mental health outcomes among hospital personnel during the Covid-19 pandemic in Taiwan

Abstract: Purpose: This study investigated the association between professional quality of life, working context, and mental health outcomes among hospital personnel in Taiwan during the worldwide upsurge in COVID-19 cases. Patients and Methods:We recruited 503 hospital personnel to whom we administered online questionnaires containing items from the Professional Quality of Life (ProQoL) scale, which covers compassion satisfaction (CS), burnout (BO) and compassion fatigue (CF), the Depression, Anxiety and Stress Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
(103 reference statements)
6
17
0
Order By: Relevance
“…According to a recent meta-review [ 10 ], our results conform to the rates of BO reported by HCWs worldwide during the third wave [ 35 ]. Additionally, these results converge to those of reports indicating low to moderate levels of STS in HCWs during the pandemic [ 32 , 36 , 37 ]. We found only two studies that examined ProQOL and its dimensions (CS, BO, STS) in MHWs during COVID-19 [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…According to a recent meta-review [ 10 ], our results conform to the rates of BO reported by HCWs worldwide during the third wave [ 35 ]. Additionally, these results converge to those of reports indicating low to moderate levels of STS in HCWs during the pandemic [ 32 , 36 , 37 ]. We found only two studies that examined ProQOL and its dimensions (CS, BO, STS) in MHWs during COVID-19 [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…The WHO-QOL was used to assess QOL among HCWs. The finding that HCWs’ QOL was affected in the physical, psychological, social, and environmental domains corroborates previous research among Greek HCWs [ 24 ] reporting associations between depression and poor QOL [ 25 ]. Mental ill-health is associated with low QOL [ 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…The WHO-QOL was used to assess QOL among HCWs. The nding that HCWs' QOL was affected in the physical, psychological, social, and environmental domains corroborates previous research among Greek HCWs [16] reporting associations between depression and poor QOL [17]. Mental ill-health is associated with low QOL [25].…”
Section: Discussionsupporting
confidence: 88%